2007
DOI: 10.1177/0969733007073693
|View full text |Cite
|
Sign up to set email alerts
|

Moral Responsibility: A Relational Way of Being

Abstract: This article reports a study exploring the meaning of the complex phenomenon of moral responsibility in nursing practice. Each of three focus groups with a total of 14 student nurses were conducted twice to gather their views on moral responsibility in nursing practice. The data were analysed by qualitative thematic content analysis. Moral responsibility was interpreted as a relational way of being, which involved guidance by one's inner compass composed of ideals, values and knowledge that translate into a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Nurses in this study identified that finding someone to talk to about the experience was a primary means for working through moral distress. This finding is in line with other researchers who point out moral identity and moral action are relational, contextual, and situational (Doane, 2002;Hardingham, 2004;Lindh, Severinsson, & Berg, 2007;Varcoe et al, 2004) and suggests that ameliorating the experience of moral distress is also relational.…”
Section: Discussionsupporting
confidence: 92%
“…Nurses in this study identified that finding someone to talk to about the experience was a primary means for working through moral distress. This finding is in line with other researchers who point out moral identity and moral action are relational, contextual, and situational (Doane, 2002;Hardingham, 2004;Lindh, Severinsson, & Berg, 2007;Varcoe et al, 2004) and suggests that ameliorating the experience of moral distress is also relational.…”
Section: Discussionsupporting
confidence: 92%
“…This increased the opportunities to enhance the understanding of the phenomenon under study more deeply. A focus group schedule was developed covering the two main areas: meaning of moral responsibility (Lindh, Severinsson, & Berg, 2007) and expressions of moral responsibility in nursing practice. The present study focuses on the latter area.…”
Section: Data Collectionmentioning
confidence: 99%
“…This, in turn, contributed to a reliance by student nurses on unreflected ethical knowledge in clinical situations. In a study of moral responsibility in nursing practice (Lindh, Severinsson, & Berg, 2007) student nurses understood that reflection together with others was important for the development of an inner compass, which in their view guided their practice.…”
Section: Introductionmentioning
confidence: 98%
“…Nurses' moral identities are dialogical, narrative, relational, and contextual, 97,98 where moral responsibility in nursing involves striving to do good in situations that are never the same twice. 99 In their everyday practice, nurses have the opportunity, when collaborating with other members of the interprofessional team, to bring forth and encourage individual and team-based ethical reflection that encompasses nurses' moral understanding of patients' experiences and needs. Furthermore, nurses should be able to articulate clearly the links between their own moral understandings of patient situations, the care they provide based on such understanding, and outcomes observed in response to such care.…”
Section: Concluding Reflectionsmentioning
confidence: 99%